MINERAÇÃO DE REGRAS DE ASSOCIAÇÃO APLICADA A DADOS DO SISTEMA DE INFORMAÇÃO AMBULATORIAL DO SUS - Schuch, Regis R.; Dill, Sérgio L.; Sausen, Paulo S.; Padoin, Edson L.; Campos, Mauricio d. (Salão do Conhecimento, 2013)
Resumo